Assessment of the Safety and Effectiveness of Emergency Department STEMI Bypass by Defibrillation-only Emergency Medical Technicians/Primary Care Paramedics. (3rd April 2015) - Ross, Garry; Alsayed, Thamir; Turner, Linda; Olynyk, Chris; Thurston, Adam; Verbeek, P. Richard
Abstract: Introduction. The American Heart Association (AHA) suggests emergency medical service (EMS) providers transporting ST-segment elevation myocardial infarction (STEMI) patients to a percutaneous coronary intervention (PCI) center require advanced life support (ALS) skills. Objectives. To evaluate the potential safety and time savings effectiveness of defibrillation-only emergency medical technician/primary care paramedic (EMT-D/PCP) EMS transport to a PCI center in a system where only emergency medical technician-paramedics/advanced care paramedics (EMT-Ps/ACPs) are authorized to bypass non-PCI hospitals.Methods. We reviewed 89 consecutive patients meeting STEMI criteria transported by EMT-Ds/PCPs per protocol by one of three paths: 1) closest non-PCI center emergency department (ED) with secondary transfer by EMT-Ps/ACPs to a PCI lab, 2) rendezvous with EMT-Ps/ACPs and diversion to a PCI lab, and 3) PCI center ED if it was closest. Actual transport times to the PCI center ED were compared to predicted transport times determined by mapping software had EMT-Ds/PCPs followed a direct path. Lastly, we recorded predefined clinically important events and advanced care interventions.Results. Twenty-seven, 51, and 11 patients followed paths 1, 2, and 3 respectively. Median transport times for path 1 were 6 (IQR 5) minutes to reach the nearest non-PCI center ED and 66 (IQR 45) minutes to the PCI center ED compared to a median predicted 13 (IQR 7) minutes to a PCI center ED had EMT-Ds/PCPs followed a direct path. Median transport time for path 2 was 12 (IQR 8) minutes compared to a median predicted time of 11 (IQR 6) minutes had no EMT-P/ACP rendezvous occurred. Median transport time for path 3 was 7 minutes (IQR 5). Three patients experienced prehospital cardiac arrest; 1 required dopamine, and 4 others received a saline bolus for hypotension. Conclusions. Substantial time savings may occur if EMT-Ds/PCPs bypass non-PCI center EDs with only a small predicted increase (about 7 minutes) in the transport time to the PCI center ED. EMT-P/ACP rendezvous does not appear to substantially increase transport time. Given the relatively low occurrence of clinically important events, our findings suggest that EMT-D/PCP bypass to a PCI center ED may be safe and effective for selected STEMI patients.